Content encapsulation in consciousness is likely to be incomplete. (2016) - Basso, Demis
Abstract: Although the passive frame theory (PST) seems to be very plausible, the encapsulation of content generation deserves further elaboration. Many concepts and data considering the capacity theory, perception, and higher cognitive processes seem to contradict this principle. In general, PST can be suitable in many cases, but it needs to be completed by other mechanisms.